Reconstructing the Music Royalty Payment Model for Micro, Small, and Medium Enterprises (UMKM) in Indonesia - Aggistri, Zayyan Syafiqah; Moody R Syailendra Putra (Al-Risalah, 2026)
The use of music in commercial activities, particularly in cafés, restaurants, and other service-oriented businesses, has intensified debates over the legal design of royalty payments in Indonesia. Although royalty obligations serve as an essential mechanism for protecting the economic rights of creators and copyright holders, the application of uniform tariff structures continues to generate concerns regarding distributive fairness, legal proportionality, and regulatory effectiveness. These concerns are especially significant for micro, small, and medium enterprises (UMKM), whose economic capacity, turnover, and intensity of music utilization vary considerably. A standardized royalty regime imposed on economically diverse business actors may create disproportionate compliance burdens and weaken the legitimacy of copyright governance. This study examines the legal construction of music royalty payments for UMKM and formulates a more equitable payment model within the Indonesian copyright framework. It employs normative legal research using statutory and conceptual approaches, focusing on copyright legislation, implementing regulations, and theories of proportionality and regulatory justice in intellectual property law. The findings indicate that the current royalty mechanism remains predominantly tariff-oriented and does not adequately accommodate differences in business scale, revenue capacity, and patterns of music exploitation. As a result, uniform tariffs risk producing unequal legal and economic consequences for UMKM. This article therefore proposes the reconstruction of a proportional and adaptive royalty payment model based on differentiated criteria, including business turnover, ability to pay, business category, and the intensity of music use. Such a framework is expected to balance the economic interests of creators with the sustainability of UMKM, while strengthening legal certainty, improving compliance incentives, and promoting a more socially responsive copyright governance regime in Indonesia.